2017
DOI: 10.1080/13683500.2017.1396294
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation, bargaining, and discounts: generating WoM and local tourism development at the Tabriz bazaar, Iran

Abstract: This paper examines the effects of negotiation intention, bargaining propensity, and discount satisfaction on word-of-mouth (WoM) behaviours for tourists visiting Tabriz bazaar, Iran. Data from 615-survey respondents highlights that tourists are motivated to conduct WoM behaviour when they are experientially satisfied with the opportunity to negotiate and bargain, and when they are satisfied with the discount they receive. This paper makes theoretical contributions to Social-Exchange-Theory and presents manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The Iranian bazaars have maintained their position as genuine social and commercial exchange points for locals, while also becoming mainstays of the country's tourist product, showcasing national heritage, culture, and craftsmanship to create unique visitor experiences (Hanachi & Yadollahi, 2011;UNESCO, 2017b). As well as being attracted to the heritage of such sites, their ambience, and the range of goods for sale, research suggests tourists also find experiential appeal in the negotiation process associated with purchases made at bazaars (Thompson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Iranian bazaars have maintained their position as genuine social and commercial exchange points for locals, while also becoming mainstays of the country's tourist product, showcasing national heritage, culture, and craftsmanship to create unique visitor experiences (Hanachi & Yadollahi, 2011;UNESCO, 2017b). As well as being attracted to the heritage of such sites, their ambience, and the range of goods for sale, research suggests tourists also find experiential appeal in the negotiation process associated with purchases made at bazaars (Thompson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research has been conducted on tourism development that exceeds the capacity of the destination using overtourism and gentrification theories [22]. Previous studies have shown that the relationship between residents and tourists is sometimes understood as an interaction between hosts and guests, and SET has been applied to study the balance between these parties [18,27]. As a result, studies show that when the expected benefits set by tourists and perceived by residents are balanced, their interactions proceed without conflict [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The United Nations 2030 Agenda for Sustainable Development (2015) (Torres, 2005;Madruga & Rojas, 2012;Payen, 2014;Thompson et al, 2018). If tourism is inserted in various urban local spaces from polyvalent cities to specialized tourism cities, then advancement on goal 11 can be achieved through integrated urban planning that incorporates sustainable approaches to tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%